High-performance Ti(C, N)-based cermet with ZrO2 whiskers and Al0.3CoCrFeNi high-entropy alloy. (December 2022) - Fang, Yihang; Xia, Lingqin; Chen, Guang; Wu, Tao; Wang, Ruiquan; Yu, Xiang; Chen, Kaimin; Zhang, Mengxian; Zhao, Xianrui; Cheng, Hu
Abstract: In this study, a high–performance Ti(C, N)-based cermet was prepared by vacuum hot-press sintering technology using Ti(C, N) as the hard phase material, WC, TaC and Mo2 C as the second-phase carbides, Al0.3 CoCrFeNi high-entropy alloy (HEA) as the metal binding phase and ZrO2 whiskers as the reinforcement phase. The effects of whiskers and the HEA on the room-temperature and high-temperature properties of cermets were studied, including oxidation resistance, hardness, bending strength, fracture toughness and frictional wear properties. The research showed that the high-temperature properties of cermets were improved by ZrO2 whiskers and HEAs compared to those of conventional cermets with Ni/Co as the binding phase. The mechanisms for the weakening of cermets at high temperatures were grain boundary softening and material oxidation. Moreover, the high-temperature strengthening mechanism was attributed to the strength of the grain boundaries in the cermet, high–temperature hardness and oxidation resistance of the HEA binding phase, as well as the strengthening of the ZrO2 whiskers at high temperatures. The results proved that the wear mechanism of cermet materials was adhesive wear at high temperatures. Highlights: High-entropy alloy Al0.3 CoCrFeNi and ZrO2 whiskers was used for the Ti(C, N)-based cermets. Room-temperature and high-temperature properties were thoroughly studied. Al0.3 CoCrFeNi metal and ZrO2 whiskers remarkably improved the properties of the cermets at high-temperature. Strengthening and weakening mechanisms for their high-temperature properties were proposed and discussed.